2020
DOI: 10.1017/s1431927620001580
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Internal Structure of a Modern Seafloor Hydrothermal Chimney With a Combination of EBSD, EPMA, and XRD

Abstract: Samples from the sphalerite-dominated zone of a seafloor massive sulfide chimney, the Satanic Mills Chimney of the PACMANUS hydrothermal field, have been investigated to determine the internal macrostructure and microstructure of this zone, the phases present, and the distribution of metals. A combination of electron probe microanalysis, electron backscattered diffraction, and x-ray diffraction has been used. At the macroscale, this zone of the chimney wall is heavily porous and is comprised primarily of sphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…The globular textures of the sphalerite clusters observed in our experiments are very similar to those observed in seafloor hydrothermal systems (Hu et al, 2019;Glenn et al, 2020) as well as the colloform textures observed in MVT ores (Roedder, 1968;Leach et al, 2005Leach et al, , 2010 and Irish-type ores (Hitzman et al, 2002). In those ores, there are multiple depositional layers and more replacement features than in our experimental products, which most likely indicates multiple episodes of carbonate dissolution and ore deposition within a compact subsurface environment.…”
Section: Discussion and Conclusion Ore Texturessupporting
confidence: 84%
“…The globular textures of the sphalerite clusters observed in our experiments are very similar to those observed in seafloor hydrothermal systems (Hu et al, 2019;Glenn et al, 2020) as well as the colloform textures observed in MVT ores (Roedder, 1968;Leach et al, 2005Leach et al, , 2010 and Irish-type ores (Hitzman et al, 2002). In those ores, there are multiple depositional layers and more replacement features than in our experimental products, which most likely indicates multiple episodes of carbonate dissolution and ore deposition within a compact subsurface environment.…”
Section: Discussion and Conclusion Ore Texturessupporting
confidence: 84%